THE MISTAKE BUSTER TECHNIQUE FOR SENTENCE CONSTRUCTION Classroom Action Research at SMPN 1 Sukasada - I.P.Y Sudarmawan; N.W Swarniti; I.K.M Susila (Universitas Pendidikan Ganesha, 2020)
This study was conducted to improve the competence of students of SMP N 1 Sukasada inconstructing Simple Present Tense sentences by applying the concept of Subject – Verb Agreementand appropriate Auxiliaries through the Mistake Buster Technique. Grammar is one of the languagecomponents that should be mastered by the students in order to develop accuracy and creativity inusing the language in communication. The findings of the study show the students’ competence inconstructing sentence is improving; it is shown by the students’ mean score which improves from cycleto cycle. From the observation, it was found that MBT allows students to find and correct mistakesthemselves which help them to understand the rules deeper.